GluN2D-containing NMDA receptors in parvalbumin neurons in the nucleus accumbens regulate nocifensive responses in neuropathic pain - Sukanya G. Gakare; Gajanan P. Shelkar; Dinesh Y. Gawande; Ratnamala Pavuluri; Pauravi J. Gandhi; Shashank M. Dravid (Neurobiology of Disease)
Neuropathic pain presents a significant challenge, with its underlying mechanisms still not fully understood. Here, we investigated the role of GluN2C- and GluN2D-containing NMDA receptors in the development of neuropathic pain induced by cisplatin, a widely used chemotherapeutic agent. Through genetic and pharmacological strategies, we found that GluN2D-containing NMDA receptors play a targeted role in regulating cisplatin-induced neuropathic pain (CINP), while sparing inflammatory or acute pain responses. Specifically, both GluN2D knockout (KO) mice and pharmacological blockade of GluN2D-containing receptors produced robust reduction in mechanical nocifensive response in CINP. In contrast, GluN2C KO mice behaved similar to wildtype mice in CINP but showed reduced mechanical hypersensitivity in inflammatory pain. Using conditional KO strategy, we addressed the region- and cell-type involved in GluN2D-mediated changes in CINP. Animals with conditional deletion of GluN2D receptors from parvalbumin interneurons (PVIs) or local ablation of GluN2D from nucleus accumbens (NAc) displayed reduced mechanical hypersensitivity in CINP, underscoring the pivotal role of accumbal GluN2D in PVIs in neuropathic pain. Furthermore, CINP increased excitatory neurotransmission in the NAc in wildtype mice and this effect is dampened in PV-GluN2D KO mice. Other changes in CINP in NAc included an increase in vGluT1 and c-fos labeled neurons in wildtype which were absent in PV-GluN2D KO mice. GiDREADD-induced inhibition of PVIs in the NAc produced reduction in mechanical hypersensitivity in CINP. These findings unveil a novel cell-type and region-specific role of GluN2D-containing NMDA receptors in neuropathic pain and identify PVIs in NAc as a novel mediator of pain behaviors.